Medición del riesgo inherente en las políticas de pago de la empresa GARAYCAM C.A. - Arias Roque, Diana Priscilla (My University, 2021)
This research is about the measurement of inherent risk, which is a financial audit tool, which through its analysis allows to know the internal or external factors of the company that are affecting the correct making of financial and business decisions. The objective is to improve the payment policies of the GARAYCAM C.A. shrimp farm. by measuring the inherent risk that refers to the fact that it can exist in an intrinsic way in each activity or procedure and cannot be eliminated, such as, for example: low prices, the weather, thefts that happen within the shrimp sector. The internal control procedures that were used for the correct application of the payment policies are the following: set out the payment policies through a manual and instructions such as, for example: the money disbursements that are made in the company on a weekly basis. The methodology that was used within the investigation is the analytical - synthetic method, likewise the empirical methods that are the interview, the document study and the observation of the company GARAYCAM C.A; The development of an internal control system for accounts payable to suppliers, contributes to the administrative, financial and accounting level of the company to optimize resources and keep an efficient control of accounts payable with suppliers, in addition it is concluded that an optimal evaluation of inherent risk is vital for the company in the shrimp sector to be able to obtain greater efficiency in the process of weekly payments that are made, to be able to update and improve the payment policies they currently have and can be planned appropriately by management the resources that are allocated weekly and avoid having financial risks in the future, so it is recommended to continue with the measurement of the inherent risk and implement the system of control of payments of accounts payable to suppliers.
Esta investigación es sobre la medición del riesgo inherente que es una herramienta de la auditoría financiera, que mediante su análisis permite conocer los factores internos o externos de la empresa que estén afectando la correcta toma de decisiones financieras y empresariales. El objetivo radica en mejorar las políticas de pago de la camaronera GARAYCAM C.A. mediante la medición del riesgo inherente que hace referencia de que puede existir de manera intrínseca en cada actividad o procedimiento y no puede ser eliminado como, por ejemplo: los bajos precios, el clima, robos que suceden dentro del sector camaronero. Los procedimientos de control interno que se utilizaron para la correcta aplicación de las políticas de pago son las siguientes: plasmar las políticas de pago a través de un manual e instructivo como, por ejemplo: los desembolsos de dinero que se hacen en la empresa semanalmente. La metodología que se utilizó dentro de la investigación es el método analítico - sintético, así mismo los métodos empíricos que son la entrevista, el estudio de documento y la observación de la empresa GARAYCAM C.A; El desarrollo de un sistema de control interno para cuentas por pagar a proveedores, aporta al nivel administrativo, financiero y contable de la empresa para optimizar recursos y llevar un eficiente control de las cuentas por pagar con los proveedores, además se concluye que una óptima evaluación del riesgo inherente es vital para la empresa del sector camaronero para poder obtener una mayor eficiencia en el proceso de los pagos semanales que se realizan, poder actualizar y mejorar las políticas de pago que tienen actualmente y se pueda planificar de forma apropiada por parte de gerencia los recursos que se destinan semanalmente y evitar tener riesgos financieros a futuros por lo que se recomienda seguir con la medición del riesgo inherente e implantar el sistema de control de pagos de cuentas por pagar a proveedores.
Keywords: RIESGO INHERENTE; AUDITORÍA FINANCIERA; POLÍTICAS DE PAGO